METAPHOR IN POLITICAL CONFLICT. POPULISM AND DISCOURSE - Dejana Vukasovic (Srpska Politička Misao)
Ruth Breeze, Carmen Llamas Saíz (eds.), Metaphor in political conflict. Populism and discourse, Ediciones Universidad de Navarra (EUNSA), Pamplona, 2020, 212 p.